Correlation between optic disc perfusion and glaucomatous severity in patients with open-angle glaucoma: an optical coherence tomography angiography study - Wang, Xiaolei; Jiang, Chunhui; Ko, Tony; Kong, Xiangmei; Yu, Xiaobo; Min, Wang; Shi, Guohua; Sun, Xinghuai (Graefe's archive for clinical and experimental ophthalmology, 2015)
Purpose To explore how optic disc perfusion varies in patients with open-angle glaucoma (OAG) and how this correlates with glaucoma severity. Methods We performed a prospective and cross-sectional observational study that included 62 eyes from 62 patients with OAG, divided into three groups according to their visual field (VF) results, and 20 eyes from 20 normal control subjects. Optic disc perfusion was studied using optical coherence tomography angiography (angio-OCT), and flow index and vessel density were determined. The VF, mean deviation (MD), pattern standard deviation (PSD), retinal nerve fiber layer (RNFL) thickness, and ganglion cell complex (GCC) thickness were also recorded. The potential associations between disc perfusion and VF defects or structural loss were analyzed. Results In OAG patients, the disc flow index and vessel density were significantly lower than in normal controls (all p<0.001) and were correlated with the severity of glaucoma. In OAG eyes, the flow index and vessel density were significantly correlated with MD, RNFL, and GCC thickness (all p<0.01), but were not in the normal controls. The receiver operating characteristic (ROC) curve analysis also revealed that disc flow index and vessel density had the power to differentiate normal eyes from eyes with OAG (under the ROC curves: 0.82 and 0.80, respectively). Conclusions Angiograms demonstrated a reduced disc flow index and vessel density in glaucoma, and this reduction was closely related to GCC thickness. This indicated that measurement of disc perfusion by angio-OCT might be important for the monitoring of glaucoma.